IRINOTECAN, FLUOROURACIL AND LEUCOVORIN IN PATIENTS WITH METASTATIC COLORECTAL CANCER - Deyan Davidov (Peytchinski Publishing, 2008)
Background: Irinotecan is a topoisomerase I inhibitor that prolongs survival as second- line therapy in patients with metastatic colorectal cancer, treated with Fluorouracil and Leucovorin only. Aim: The aim of this study was to evaluate the efficacy and toxicity of the combination Irinotecan, Fluorouracil and Leucovorin. Methods: In the period 2006- 2007 34 patients with metastatic colorectal cancer entered the study. The treatment schedule consists of Irinotecan 180 mg/m2 day 1, Fluorouracil 400 mg/m2 day 1 and 2 and Leucovorin 200 mg/m2 day 1 and 2 every 14 days. Results: Overall response rate was 36,7% with three complete remissions. Median survival was 20,3 months. Diarrhea, vomiting and mucositis were most common side effects. Conclusions: That data suggest that the addition of Irinotecan to Fluorouracil and Leucovorin will offer opportunity to treat patients with metastatic colorectal cancer.